Against Cartography: Decoloniality in the Lacanian Account of Transference in Seminar XI - Ahmad Fuad Rahmat (EJP import test, 2022)
Summary: This paper considers the decolonial potential in the Lacanian account of transference through revisiting how Lacan accounts for the deceptiveness of the visual field in Seminar XI by historicising the imaginary. Of particular significance is his reference to the anamorphosis in Hans Holbein’s The Ambassadors to describe the gaze, a reference which brings the early modern rivalry among European empires and their global pursuit of colonies into Lacan’s view. In doing so it renders the gaze, and the lack in the subject’s desire to see, as the essence of empire. My argument stresses this by showing how Lacan also uses his reading of the painting as an occasion to discuss the Cartesian subject’s cartographic quality, wherein geometral visual domination, which underlies Western visual culture and civilization and their imperial implications, functions through the subsumption of sight into space. My conclusion briefly reflects on what this means for the relationship between Lacan and coloniality.
Keywords: decoloniality; Lacan; mapping; seminar; The Gaze